On the nature of DNA-duplex stability - Rezác, Jan; Hobza, Pavel (Chemistry (Weinheim an der Bergstrasse, Germany), 2007)
The unwinding free energy of 128 DNA octamers was correlated with the sum of interaction energies among DNA bases and their solvation energies. The former energies were determined by using the recently developed density functional theory procedure augmented by London dispersion energy (RI-DFT-D) that provides accurate hydrogen-bonding and stacking energies highly comparable with CCSD(T)/complete basis set limit benchmark data. Efficient tight-binding DFT covering dispersion energy was also used and yielded satisfactory results. The latter method can be used for extended systems. The solvation energy was determined by using a C-PCM continuum solvent at HF level calculations. Various models were adopted to correlate theoretical energies with experimental unwinding free energies. Unless all energy components (hydrogen-bonding, intra- and interstrand-stacking, and solvation energies) were included and weighted individually, no satisfactory correlation resulted. The most advanced model yielded very close correlation (RMSE=0.32 kcal mol(-1)) fully comparable with the entirely empirical correlation introduced in the original paper. Analysis of the theoretical results shows the importance of inter- and intramolecular stacking energies, and especially the latter term plays a key role in determining DNA-duplex stabilization.
Keywords: algoritmy; Hydrogen Bonding; DNA; vodíková vazba; termodynamika; Nucleic Acid Conformation; Thermodynamics; vazebná místa; Algorithms; Binding Sites; konformace nukleové kyseliny